Effect of Planting Method on Mustard Boro Inter Mixed Cropping System (Bangladesh Agronomy Journal, 2019)
A field experiment was carried out at Multi Location Testing (MLT) site, Debiddar and Chandpur during Rabi season of 2015-16 to find out the suitable boro rice planting method with cost and return of inter mixed cropping system in Cumilla region. The treatment combinations used were T1 : Boro rice (broadcast) + Mustard, T2 : Boro rice (Line sowing) + Mustard, T3 : Sole Mustard, T4 : Sole boro rice. Results revealed that all the mixed cropping combinations showed superior in terms of gross return, gross margin and rice equivalent yield (REY) than sole cropping. The highest rice equivalent yield (8.52 t ha-1) was found in the treatment combination of boro rice line sowing + mustard. From the cost and return analysis it was observed that the combination of boro rice line sowing with mustard (T2) gave the highest gross return (Tk. 127800 ha-1) and gross margin (Tk. 77400 ha-1) where sole crop of mustard (T3) gave the lowest gross return (Tk. 65120 ha-1) and gross margin (Tk. 21450 ha-1) which indicated the advantage of mixed cropping over the soleBangladesh Agron. J. 2018, 21(2): 45-48